HER2 testing in the UK: recommendations for breast and gastric in-situ hybridisation methods. Issue 8 (20th June 2011) - Bartlett, J M S; Starczynski, J; Atkey, Neil; Kay, E; O'Grady, A; Gandy, Michael; Ibrahim, Merdol; Jasani, Bharat; Ellis, I O; Pinder, S E; Walker, R A
Abstract : These guidelines supplement existing guidelines on HER2 testing by immunohistochemistry and in-situ hybridisation(ISH) methods in the UK. They provide a specific focus on aspects of guidance relevant to HER2 ISH testing methods, both fluorescent and chromogenic. They are formulated to give advice on methodology, interpretation and quality control for ISH-based testing of HER2 status in common tumour types, including both breast and gastric tumours. The aim is to ensure that all ISH-based testing is accurate, reliable and timely.